PENGELOLAAN SISTEM SARAN DI ORGANISASI PENDIDIKAN: DIINPIRASI OLEH ORGANISASI BISNIS - Suang, Lei (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The ways to achieve desired quality result in educational organization that mostly inspired from the business organizations was no doubt anymore. How the view was appropriate in the implementation of a Suggestion System was the focus of our study. The study aimed to (i) comprehend reasoning the system was adopted, (ii) to draw up how the system was implemented, and (iii) to present potential areas affected by a system. The study was conducted at the Global Andalan and Taruna Andalan School in Pelalawan Riau Indonesia. The school was owned by famous company in Riau, namely Pulp and Paper Company in Riau (PT RAPP), and was managed under the Foundation of Kerinci Citra Kasih. To collect the data, we designed questionnaires, documentation analysis and interviewed both teachers and school managements involved in the Suggestion System. We found that the reason the system was adopted was due to empower employees, including teachers, yet improve quality service. The system was implemented on the basis of four major steps: Encouraging People to participate, Motivate employee to write proposals, Review evaluate and guidance, and Awards. We also found other potential improvement by the system implementation on employee empowerment.Keywords: Education, School, Continuous improvement, Suggestion system, Employee empowerment